Dietary energy requirement of piracanjuba fingerlings, Brycon orbignyanus, and relative utilization of dietary carbohydrate and lipid - Borba, M. R. [UNESP]; Fracalossi, D. M.; Pezzato, L. E. [UNESP] (Hindawi, 2006)
Ten isonitrogenous casein-gelatin-based diets were formulated to contain five estimated metabolizable energy concentrations (10.92, 12.29, 13.63, 14.82 and 16.16 kJ g -1) at two carbohydrate-to-lipid ratios (CHO : L, 5.3 and 12.8, g : g) in a 5 × 2 factorial arrangement. Each diet was assigned to triplicate groups of 11 piracanjuba fingerlings (5.25 ± 0.14 g) and fed to apparent satiation twice a day for 90 days. Higher daily weight gain was obtained by fish fed the 13.63 kJ g -1 diets for both CHO : L ratios. There was a significant reduction of feed consumption when dietary energy concentration increased above 13.63 kJ g -1. Feed conversion ratio and apparent net energy retention improved as dietary energy increased. Apparent net protein retention tended to be lower in the highest and lowest dietary energy concentrations. The results suggest that dietary lipid energy was more efficiently utilized by piracanjuba fingerlings than carbohydrate energy. Body composition and hepatosomatic index (HSI) were not influenced by dietary CHO : L ratio. However, an increase in dietary energy concentration beyond 13.63 kJ g -1 resulted in a significant increment in lipid deposition, while body moisture and HSI decreased. Our findings indicate that at 300 g kg -1 dietary crude protein, a CHO : L ratio of 5.3 is recommended for piracanjuba, and the required energy is either 13.63 kJ g -1 if raised for aquaculture or 14.82 kJ g -1 if destined to stock enhancement. © 2006 Blackwell Publishing Ltd.
Keywords: Body composition; Brycon orbignyanus; Carbohydrate-to-lipid ratio; Energy requirement; Growth; Piracanjuba